دراسة تحليلية لتطور الزمن الحقيقي في نظرية المعايرة (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
قُسمت حقول المعايرة إلى صيغ متجانسة وصيغ غير متجانسة، ثم كوملت الصيغ غير المتجانسة وكانت نتائج هذه التكاملات ثوابت عددية. وبدورنا طبقنا تمثيل فغنر على الصيغ المتجانسة المتبقية. حسبنا تطور الزمن الحقيقي للقيمة المتوقعة لأي مؤثر حتى التصحيح الكمومي الأول، تعالج هذه الطريقة نظرية المعايرة عندما يكون مربع ثابتة الإرتباط 12g2L">  صغيراً أي عندما لايمكن تطبيق نظرية الإضطراب. Fields gauge have been divided into homogeneous modes and inhomogeneous modes; they have then been integrated the inhomogeneous modes. The results of these integrals were numerical constants. We then applied Wigner`s formalism on remained homogeneous modes. We found the real time evolution to the expectant value for any operator up to the first quantum correction. This method deals the gauge theory; when the square of connection constant  is small. That means we can not apply the perturbation theory.